CMV Disease in IBD: Comparison of Diagnostic Tests and Correlation with Disease Outcome. Issue 7 (30th April 2018) - Johnson, Jessica; Affolter, Kajsa; Boynton, Kathleen; Chen, Xinjian; Valentine, John; Peterson, Kathryn
Abstract: Background: Significance of cytomegalovirus (CMV) in inflammatory bowel disease (IBD) is unclear due to pathobiology, numerous CMV tests, and disparate treatment outcomes. Methods: Retrospective chart review was done on patients with positive qualitative CMV tissue polymerase chain reaction (PCR) from 2005–2013 at a tertiary referral hospital. Frequency of PCR+, hematoxylin and eosin staining(HE)+, histopathology and immunohistochemistry (IHC)+ was assessed. IHC was assessed on a sample of PCR- tissues. Surgery rates were correlated with CMV testing and treatment. Results: PCR was done on 310 samples from 180 patients. Thirty-seven samples were PCR+ (51.4% PCR+ only, 35.1% IHC/PCR+, 13.5% HE/IHC/PCR+). The H&E frequently failed to detect CMV identified on extensive IHC. Of 13 PCR- samples tested with IHC, 100% were negative. Twenty-five patients were CMV+ (40% PCR+, 40% IHC/PCR+, 20% HE/IHC/PCR+). Surgery rates increased with number of positive tests: 60% in IHC/PCR+ and 80% in HE/IHC/PCR+, compared to 26.8% in PCR- or PCR+ ( P = 0.03, P = 0.02, respectively). There were 20/25 PCR+ patients who received CMV treatment. Surgery occurred in 80% of HE+ patients despite treatment and 100% of IHC+ patients without treatment. Conclusions: Rates of CMV+ testing and surgical risk varied by test modality. PCR+ results were most frequent but alone did not detect clinically significant CMV. HE+ testing was least frequent and associated with highest surgical rate, despite treatment. CMV treatment may benefit IHC+ patients most, supporting immunostaining as optimal diagnostic test for clinically significant CMV in IBD. In PCR+ samples, HE frequently did not detect CMV identified on extensive IHC. In PCR- samples, data suggest IHC is likely negative. Consider using qualitative PCR to guide extensive immunostaining.